Arterial Stiffness and Diabetes Risk in Framingham Heart Study and UK Biobank. Issue 6 (10th August 2022) - Cohen, Jordana B.; Mitchell, Gary F.; Gill, Dipender; Burgess, Stephen; Rahman, Mahboob; Hanff, Thomas C.; Ramachandran, Vasan S.; Mutalik, Karen M.; Townsend, Raymond R.; Chirinos, Julio A.
Abstract : Background: Microvascular damage from large artery stiffness (LAS) in pancreatic, hepatic, and skeletal muscles may affect glucose homeostasis. Our goal was to evaluate the association between LAS and the risk of type 2 diabetes using prospectively collected, carefully phenotyped measurements of LAS as well as Mendelian randomization analyses. Methods: Carotid-femoral pulse wave velocity (CF-PWV) and brachial and central pulse pressure were measured in 5676 participants of the FHS (Framingham Heart Study) without diabetes. We used Cox proportional hazards regression to evaluate the association of CF-PWV and pulse pressure with incident diabetes. We subsequently performed 2-sample Mendelian randomization analyses evaluating the associations of genetically predicted brachial pulse pressure with type 2 diabetes in the UKBB (United Kingdom Biobank). Results: In FHS, individuals with higher CF-PWV were older, more often male, and had higher body mass index and mean arterial pressure compared to those with lower CF-PWV. After a median follow-up of 7 years, CF-PWV and central pulse pressure were associated with an increased risk of new-onset diabetes (per SD increase, multivariable-adjusted CF-PWV hazard ratio, 1.36 [95% CI, 1.03–1.76]; P =0.030; central pulse pressure multivariable-adjusted CF-PWV hazard ratio, 1.26 [95% CI, 1.08–1.48]; P =0.004). In United Kingdom Biobank, genetically predicted brachial pulse pressure was associated with type 2 diabetes, independent of mean arterial pressure (adjusted odds ratio, 1.16 [95% CI, 1.00–1.35]; P =0.049). Conclusions: Using prospective cohort data coupled with Mendelian randomization analyses, we found evidence supporting that greater LAS is associated with increased risk of developing diabetes. LAS may play an important role in glucose homeostasis and may serve as a useful marker of future diabetes risk.